Strategies to improve the stress resistance of Escherichia coli in industrial biotechnology. (20th April 2022) - Tao, Yuxuan; Wang, Hanxiao; Wang, Jingnan; Jiang, Wankui; Jiang, Yujia; Xin, Fengxue; Zhang, Wenming; Jiang, Min
Abstract: The use of industrial Escherichia coli strains for the production of bio‐based chemicals offers a promising and sustainable solution to a growing scarcity of non‐renewable resources and contributes to the protection of the environment. However, many limitations, such as inhibition from toxic substrates, hyperosmosis, toxic by‐products, and other adverse fermentation conditions, prevent strains from attaining a stable cell growth rate, efficient metabolic flux, and satisfactory productivity. There has thus been much effort to obtain E. coli strains that exhibit robust growth and productivity with enhanced tolerance of extreme operating conditions. In this review, we gained insights into recent studies in improving tolerance of E. coli and summarized four kinds of engineering methods: modifying regulation factors, regulating membrane structure, optimizing biosynthetic pathways, and applying adaptive evolution. The combination of different engineering strategies therefore provided a broader platform for robustness of industrial E. coli, making further steps to achieving more advantageous biosynthesis. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd